Evaluation of the effectiveness and safety of combining PD-1/PD-L1 inhibitors with anti-angiogenic agents in unresectable hepatocellular carcinoma: a systematic review and meta-analysis - Zhu, Hengzhou; Zhao, Wenyue; Chen, Haoyan; Zhu, Xiaodan; You, Jianliang; Jin, Chunhui (Frontiers in Immunology, 2024)
Background: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality globally, particularly when diagnosed at an unresectable stage. Traditional treatments for advanced HCC have limited efficacy, prompting the exploration of combination therapies. This systematic review and meta-analysis evaluate the effectiveness and safety of combining PD-1/PD-L1 inhibitors with anti-angiogenic agents in patients with unresectable HCC. Methods: A comprehensive literature search was conducted in PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and Web of Science, including studies up to June 2024. Randomized controlled trials (RCTs) comparing combination therapy (PD-1/PD-L1 inhibitors with anti-angiogenic agents) to monotherapy or standard treatments in unresectable HCC patients were included.Data were synthesized using random-effects models, with pooled hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), and risk ratios (RRs) for objective response rate (ORR) and adverse events (AEs).Results: Five Phase III RCTs involving 1515 patients were included. Combination therapy significantly improved OS (HR: 0.71, 95% CI: 0.60-0.85) and PFS (HR: 0.64, 95% CI: 0.53-0.77) compared to monotherapy or standard treatments. The pooled OR for ORR was 1.27 (95% CI: 1.57-2.11), indicating a higher response rate with combination therapy. However, the risk of AEs was also higher in the combination therapy group (RR: 1.04, 95% CI: 1.02-1.06). Subgroup analyses revealed consistent benefits across different types of PD-1/PD-L1 inhibitors and anti-angiogenic agents, with no significant publication bias detected.The combination of PD-1/PD-L1 inhibitors with anti-angiogenic agents offers significant benefits in improving OS and PFS in patients with unresectable HCC, although it is associated with an increased risk of adverse events.